Perancangan Sistem Informasi Pemesanan Tiket Travel pada CV. Jambi Permata Berbasis Web - Muhammad Habib Mustofa; Andreo Yuderth; Sepriano Sepriano (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
CV Jambi Permata is located at Jln. Kapten Pattimura No.116, Kenali Besar, Kec. Kota Baru, Jambi City, is a public service facility engaged in travel services. Based on a survey conducted by the author, directly to the location of CV. Jambi Permata. The author finds obstacles caused by the current business process, namely making it difficult for prospective passengers when they have to go directly to the location to find out the availability of travel ticket stock, so that when the ticket runs out, prospective passengers are forced to look for another travel service. Prospective customers must come more than once to the administration to find out the departure schedule, just to adjust the passenger's planned departure schedule. Making it difficult for administration to find customer data and customer departure schedules through books, where the data is already very large. Making it difficult for administration admins to recap data to be made into reports, because they have to check the entire history of previous transactions. then the solution the author offers is able to improve administrative performance in managing reservation data and make it easier for prospective passengers to place orders. The travel ticket booking information system that will be proposed presents more accurate, timely and relevant information. So that with this information, the leadership of CV. Jambi Permata can predict conditions or needs in the future better and can make decisions and can take the best actions for the progress of the business being run.